2010
DOI: 10.1118/1.3460316
|View full text |Cite
|
Sign up to set email alerts
|

Deformable lung registration between exhale and inhale CT scans using active cells in a combined gradient force approach

Abstract: The results show that the proposed method can accurately register lungs with large deformations and can considerably reduce the processing time. The proposed deformable registration technique can be used for quantitative assessments of air trapping in obstructive lung disease and for tumor motion tracking during the planning of radiotherapy treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…To correct positional differences and local deformation of the lungs, the lungs on WO images were globally aligned to the WI image using affine registration based on narrow-band distance propagation, and affine-transformed lungs were nonlinearly deformed by a demon algorithm using a combined gradient force and active cells (21). Then, each pixel in the WI and WO images was assigned to one of the three attenuation types through Equation 1 (below).…”
Section: Methodsmentioning
confidence: 99%
“…To correct positional differences and local deformation of the lungs, the lungs on WO images were globally aligned to the WI image using affine registration based on narrow-band distance propagation, and affine-transformed lungs were nonlinearly deformed by a demon algorithm using a combined gradient force and active cells (21). Then, each pixel in the WI and WO images was assigned to one of the three attenuation types through Equation 1 (below).…”
Section: Methodsmentioning
confidence: 99%
“…We note specifically here that the 4D-CT registration [20][21][22][23] and the follow-up registration are two different tasks. The chest CT examinations involved in the 4D-CT registration typically have many similar characteristics (e.g., time gap in scanning, dose, image quality, reconstruction resolution, and scanning pose) and their major difference lies in the lung shape as a result of different respiratory states.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why an affine registration is typically used as an initialization procedure for the nonrigid models in 4D-CT registration. 20 The nonrigid model may work well only if they can robustly avoid being trapped in local minima.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al,31 suggesting a variant of SSD cost function (SSTVD), reported registration accuracy ranging from 0.56 to 1.90 mm. Yim et al,18 using an endinhale end-exhale protocol, reported an accuracy of 2.8 mm. Hong et al9 using end-inspiration protocol for lung nodules F.…”
mentioning
confidence: 98%